HUMAN EXPLOITATION OF NATURE IN THE PERSPECTIVE OF CHRISTIAN ETHICS AND ESCHATOLOGY: A THEOLOGICAL STUDY OF THE CONTEMPORARY ECOLOGICAL CRISIS - Yusak Sanjaya; Jessica Elizabeth Abraham (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The contemporary ecological crisis, characterized by the massive exploitation of nature, raises fundamental theological questions regarding the relationship between humanity, God, and creation. This article aims to examine human exploitation of nature through the perspectives of Christian ethics and eschatology, positioning the ecological crisis as an ethical and eschatological issue of faith. Utilizing a qualitative-descriptive method with a critical-theological approach, this study conducts a literature review of Biblical texts, theological treatises, and Indonesian contextual theology. The findings indicate that the exploitation of nature reflects a human failure to fulfill God’s mandate of stewardship over creation and reveals a crisis in Christian ethics that is both personal and structural. Christian ethics asserts that obedience to God is manifested not only through vertical relationships but also through concrete responsibility toward communal life, including the natural world. Furthermore, Christian eschatology is understood not as a narrative of apocalyptic fear, but as a transformative and ethical hope for the restoration of creation. Eschatological hope calls believers and the church to actively engage in environmental preservation and restoration as part of their witness of faith in a wounded world. This article concludes that Christian ethics and eschatology are inseparable in responding to the ecological crisis. The exploitation of nature is not a sign of destruction to be passively accepted; rather, it serves as a prophetic call for the church to live faithfully and responsibly, participating in God’s redemptive work over all creation.